Role of Melatonin in Management of COVID-19: A Systematic Review - Ghada Essam El-din Amin; Salwa Mostafa Mohammad Abdel Rahman; Rehab Mohamed Ali Mohamed; Mohamed Farouk Allam (Microbes, Infection and Chemotherapy, 2024)
Background: the COVID-19 pandemic has significantly impacted global healthcare and economic systems. The clinical manifestation of the disease varies from flu-like symptoms to severe pneumonia and, in some cases, death. Melatonin and its metabolites play a crucial role in immunomodulation and possess anti-oxidative properties, capable of directly and indirectly scavenging reactive oxygen species. Objective: the aim of the present systematic review was to assess the effectiveness of melatonin in the management of COVID-19 patients and its role in expediting the return of patients to their baseline health. Methodology: the literature review was conducted up to August 2022, resulting in the identification of 533 articles after sorting them by authors and year of publication. Following the removal of 223 duplicate articles, 310 abstracts were screened, leading to the exclusion of 281. Subsequently, 29 full-text studies were evaluated for eligibility, with 22 being excluded. Finally, seven studies met the inclusion criteria and were included for further qualitative and quantitative analyses. Results: the findings revealed a noteworthy reduction in hospital stay among patients who received melatonin compared to those who received a placebo (standardized mean difference: -0.50, Standard error: 0.15, 95% CI: -0.80, -0.20, P value: 0.001). Melatonin was associated with a significant decrease in mortality in COVID-19 patients when compared to the placebo (Pooled RR: 0.21, 95% CI: 0.08, 0.56, P value: 0.002). However, there were no significant differences between melatonin and placebo regarding the need for hospitalization, ICU admission, artificial ventilation, and the requirement for oxygen therapy. Conclusion: melatonin may decrease the mortality rate among patients with COVID-19. Melatonin may reduce the duration of hospital stay in patients with COVID-19. Melatonin had no effect on the following outcomes in COVID-19 patients: the need for hospitalization, ICU admission, artificial ventilation and the need for oxygen therapy.